Tuning electronic ground states by using chemical pressure on quasi-two dimensional beta ''-(BEDT-TTF)(4)[(H3O)M(C2O4)(3)]center dot Y - Coldea, A; Bangura, A; Singleton, J; Ardavan, A; Akutsu-Sato, A; Akutsu, H; Day, P (2006)
We report high-field magnetotransport studies on quasi-two dimensional beta"-(BEDT-TTF)(4)[(H3O)M(C2O4)(3)]Y-. where Y is a solvent in the anionic layer. By changing the size of the solvent the low temperatures electronic behaviour varies from superconducting (for larger solvents, Y=C6H5NO2 and C6H5CN) to metallic (for smaller solvents, Y=C5H5N and CH2O2). These changes in the ground state are connected with modifications of the Fermi surface, which varies from having one or two pockets for the superconducting charge-transfer salts to at least four pockets in the case of metallic ones. When superconducting, the materials have very large in-plane critical fields (up to 32 T) and enhanced effective masses compared with the metallic compounds. The role of the charge-order fluctuations in stabilizing the superconducting ground state and the effects of intrinsic local disorder is discussed.